Equine G3P[3] rotavirus strain E3198 related to simian RRV and feline/canine-like rotaviruses based on complete genome analyses. - Miño, Samuel (2013)
Equine group A rotavirus (RVA) strains are the most important cause of gastroenteritis in equine neonates and foals worldwide, and G3P[12] and G14P[12] are epidemiologically the most important genotypes. The genotype constellation of an unusual Argentinean G3P[3] RVA strain (RVA/Horse-wt/E3198/2008/G3P[3]) detected in fecal samples of a diarrheic foal in 2008 was shown to be G3–P[3]–I3–R3–C3–M3–A9–N3–T3–E3–H6. Each of these genotypes has been found typically in feline and canine RVA strains, and the genotype constellation is reminiscent to those of Cat97-like RVA strains. However, the phylogenetic analyses revealed only a distant relationship between E3198 and known feline, canine and feline/canine-like human RVA strains. Surprisingly, a rather close relationship was found between E3198 and simian RVA strains RVA/Simian-tc/USA/RRV/1975/G3P[3] for at least 5 gene segments. RRV is believed to be a reassortant between a bovine-like RVA strain and a RVA strains distantly related to feline/canine RVA strains. These analyses indicate that E3198 is unlikely to be of equine origin, and most likely represents a RVA interspecies transmitted virus, possibly in combination with one or more reassortments, from a feline, canine or related host species to a horse. Further studies are in progress to evaluate if this strain was a single interspecies transmission event, or if this strain started to circulate in the equine population.